ESTIMATION OF ENERGY SECURITY OF AZERBAIJAN REPUBLIC WITH DUE ACCOUNT OF TENDENCY INFLUENCE ON INDICATORS’ CHANGES - V. Kh. Nasibov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
This paper describes a method for assessing the development of the energy security equation using the relationship indicators. It is shown that, instead of the eigenvalues of the diagonal indicators can use these indicators, the functional dependence on the time.